Peran Teman Sebaya dalam Pembentukan Karakter Kedisiplinan Siswa Kelas II SDIT Al-Fityah Pekanbaru - Mutiara Khairunnisa; Viona Afrila; Yusnidar Siregar; Tiara Islamiati; Wismanto Wismanto (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
Peers play a very important role in character formation, especially students' disciplined character. One of the roles of peers is to provide encouragement or motivation to other friends. The aim of this research is to find out the role of peers in forming disciplined character and the impact of the role of peers. The method in this research uses descriptive qualitative methods using words or narratives to analyze and describe certain phenomena. The results of this research are that peers can help in forming a disciplined character, in the end a person must have internal motivation and personal commitment to remain disciplined.